Pitfalls in Pathology—Nodular Hyperplasia of Bartholin's Gland. (April 2022) - Bilek, Melissa; Barrett, Theodore; Casey, Stephanie; Heller, Debra S.
Nodular hyperplasia of the Bartholin's gland is an underreported and extremely rare entity that presents as a solid lesion potentially raising concern for malignancy clinically, most solid lesions at this location are carcinomas. They may also be mistaken for a Bartholin cyst clinically. Nodular hyperplasia is rarer than carcinoma of the Bartholin gland, and hence pathologists may not be familiar with this entity, making it a pitfall in pathologic as well as a clinical diagnosis. Here we report a case originally considered a Bartholin cyst, but raising intraoperative concern due to solid elements. Histological examination of the lesion revealed nodular hyperplasia of Bartholin's gland. Recognition of this entity is important, as it is something that may be encountered by the pathologist.